Kingdom Come: The Politics of Faith and Freedom in Segregationist South Africa and Beyond - Masango Chéry, Tshepo (Religious Cultures of African and African Diaspora People 47, 2023)
In Kingdom Come, Tshepo Masango Chéry charts a new genealogy of early twentieth-century Black Christian activists who challenged racism in South Africa before the solidification of apartheid by using faith as a strategy against global racism. Masango Chéry traces this Black freedom struggle and the ways that South African church leaders defied colonial domination by creating, in solidarity with Black Christians worldwide, Black-controlled religious institutions that were geared toward their liberation. She demonstrates how Black Christians positioned the church as a site of political resistance and centered specifically African visions of freedom in their organizing. Drawing on archival research spanning South Africa, Zimbabwe, Kenya, the United Kingdom, and the United States, Masango Chéry tells a global story of the twentieth century that illuminates the formations of racial identity, state control, and religious belief. Masango Chéry’s recentering of South Africa in the history of worldwide Black liberation changes understandings of spiritual and intellectual routes of dissemination throughout the diaspora